IDENTIFIKASI POTENSI GERAKAN TANAH MENGGUNAKAN ANALISIS STATISTIK BIVARIATE PADA SISTEM INFORMASI GEOGRAFIS DI DESA CIASMARA, BOGOR - Kusuma, Fanny; Arico, Yusuf; Yan Satriyo; Dimas Wijaya; Moh. Ardhi Afnan; Misbahudin (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2023)
Mass movements often occur in the village of Ciasmara, Pamijahan district, Bogor regency. The phenomenon of mass movement can provide economic losses as well as casualties. Therefore, the village community needs to know the region's potential for a mass movement. Ciasmara village has characteristics of steep slopes and lithological arrangement that has experienced weathering. The high rain intensity also aggravates this condition; it can cause mass movements. In this community service activity, statistical analysis of Geographic Information Systems has been conducted in digitally mapping the potential of mass movement in Ciasmara village, Pamijahan, Bogor. As a data input, landslides and slope impact points from Landsat 8 were used. As a result, 212 landslide points have been collected as an inventory. This data is broken down into training data, 60% of the overall data, and the rest as validation data. The modelling results showed the correlation of landslide events with an Area Under Curve (AUC) value>0.6. After validation, the model accuracy rate of up to 81.11% indicates that the model can be accepted. This community service resulted in a land movement vulnerability map in Ciasmara village with a vulnerability level of 4 zones; the vulnerability level is very low, low, medium, and high.